The Elias University Hospital Approach: A Visual Guide to Ultrasound-Guided Botulinum Toxin Injection in Spasticity: Part III—Proximal Lower Limb Muscles - Marius Nicolae Popescu; Claudiu Căpeț; Cristina Beiu; Mihai Berteanu (Toxins)
Ultrasound-guided botulinum toxin type A (BoNT-A) injections have become an essential tool in the management of lower limb spasticity. Following our previous work, which focused on upper limb muscles, this third part provides a detailed visual guide to the identification and injection of proximal lower limb muscles frequently involved in spastic gait and posture disorders. This guide presents the ultrasound anatomy, clinical relevance, and injection strategies for eleven key muscles: gluteus maximus, piriformis, psoas major, rectus femoris, sartorius, gracilis, adductor longus, adductor magnus, semimembranosus, semitendinosus, and biceps femoris. For each muscle, the Elias University Hospital (EUH) model is applied, highlighting the zones of maximum thickness and motor point density to ensure precise and effective BoNT-A delivery. Enhanced with high-resolution ultrasound images and dynamic scanning techniques, this visual guide supports clinicians in performing safe, targeted injections. It serves as both an educational and practical reference for the ultrasound-guided treatment of spasticity in the proximal lower limb, completing the series and offering a standardized framework for comprehensive BoNT-A management. By promoting accurate toxin delivery, this approach is expected to improve functional mobility, reduce spasticity-related complications, and optimize patient-centered outcomes in rehabilitation settings.